Dynamic Instability of MRE Embedded Soft Cored Sandwich Beam with Non-Conductive Skins - S.K. Dwivedy; M. Srinivas (Shock and Vibration)
In this work the governing temporal equations of motions with complex coefficients have been derived for a three-layered unsymmetric sandwich beam with nonconductive skins and magnetorheological elastomer (MRE) embedded soft-viscoelastic core subjected to periodic axial loads using higher order sandwich beam theory, extended Hamilton's principle, and generalized Galerkin's method. The parametric instability regions for principal parametric and combination parametric resonances for first three modes have been determined for various end conditions with different shear modulus, core loss factors, number of MRE patches and different skin thickness. This work will find application in the design and application of sandwich structures for active and passive vibration control using soft core and MRE patches.